Volatile organic compounds and air toxics in northern Colorado - Low, Lena, author; Fischer, Emily V., advisor; Collett, Jeffrey L., Jr., advisor; Malin, Stephanie A., committee member (Colorado State University. Libraries, 2025)
The Colorado Northern Front Range (CNFR), stretching from Denver to Fort Collins, has significant air pollution challenges. Regional pollution sources include volatile organic compounds (VOCs) from urban activities, oil and gas (O&G) exploration and production, biogenic emissions, and wildfire smoke. The CNFR has been repeatedly designated as a nonattainment area for ozone, making reductions in VOCs and nitrogen oxides emissions a priority. Hazardous air pollutant (HAP) exposure concerns have also increased with concurrent population growth and expanding O&G production, frequently in close proximity. Sensitive populations and disproportionately impacted communities are at increased risk from air pollution exposure. While prior studies have characterized the composition and sources of air toxics and other VOCs in the southern CNFR, we extend focus to the northern portion of the region. Leveraging spatially arrayed samples, we present VOC measurements from whole air canister samples collected at eight sites during 2015-2016 and 2022-2025. This analysis includes sites near O&G wells, a large gas station, an urban school, and a suburban site at the base of the Rocky Mountains. We find strong seasonal trends that are driven by meteorological and emission patterns. Laboratory compositional analyses of gasoline and diesel fuel reveal that the ambient gas station samples exhibit a distinct VOC signature indicative of fuel volatilization. Positive matrix factorization analysis shows four source factors best describe sample VOC composition across the region: O&G activity, traffic + urban combustion, fueling station, and biogenic + background. Reflecting the regional distribution of O&G activity, there is a strong eastward increasing gradient in light alkanes and other compounds associated with O&G emissions. Highlighting the influence from traffic and fuel evaporation, the gas station has the largest ambient HAPs concentrations. Providing a rare opportunity to characterize a large uncontrolled pollution event in a rural town, we collected VOC measurements in rapid response to the largest documented O&G spill in Colorado. Observations indicate that the emission plume from a well blowout event near Galeton, CO traveled several miles downwind of the well with high HAPs concentrations, increasing potential acute exposure to residents. Together our measurements add to the growing discussion of potential for chronic and acute air toxics exposure in the CNFR.
Keywords: air toxics; oil and gas; air quality; volatile organic compounds; Colorado northern Front Range